2021
DOI: 10.3390/ma14164593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laser Spot Size on the Mechanical Properties of AISI 420 Stainless Steel Fabricated by Selective Laser Melting

Abstract: The purpose of this study is to investigate the effects of laser spot size on the mechanical properties of AISI 420 stainless steel, fabricated by selective laser melting (SLM), process. Tensile specimens were built directly via the SLM process, using various laser spot diameters, namely 0.1, 0.2, 0.3, and 0.4 mm. The corresponding volumetric energy density (EV) is 80, 40, 26.7, and 20 J/mm3, respectively. Experimental results indicates that laser spot size is an important process parameter and has significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The rapid melting and solidification processes involved several crystallization processes, which led to the formation of observable micrograins, as shown in Figure 8a. Within each micrograin, several distinct subgrains and laths could be observed, which are consistent with the findings reported in the literature [8,32,33]. The average size of the micrograins and subgrains was estimated to be around 11 ± 3 µm and 1.2 ± 0.4 µm, respectively.…”
Section: Microstructures Of Slm Samplessupporting
confidence: 91%
“…The rapid melting and solidification processes involved several crystallization processes, which led to the formation of observable micrograins, as shown in Figure 8a. Within each micrograin, several distinct subgrains and laths could be observed, which are consistent with the findings reported in the literature [8,32,33]. The average size of the micrograins and subgrains was estimated to be around 11 ± 3 µm and 1.2 ± 0.4 µm, respectively.…”
Section: Microstructures Of Slm Samplessupporting
confidence: 91%
“…There are numerous AM process variables, e.g., beam parameters [ 1 , 2 , 3 ], scanning parameters (pattern, speed, power) [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], powder characteristics and distribution [ 11 , 12 , 13 ], which can induce internal defects and largely affect the surface roughness. For example, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al. [ 1 ] showed that balling, un-overlapped defects, large re-heated zone, and large sub-grain size occur due to use of a large laser spot with low volumetric energy density in LPBF manufacturing of AISI 420 stainless steel (SS) parts. Whip et al.…”
Section: Introductionmentioning
confidence: 99%
“…Note that 420 martensitic stainless steel has also been of significant interest in SLM, since its properties are suitable for specific applications, due to its high strength and corrosion resistance [ 18 ]. Consequently, many studies have been published concerning the microstructure, mechanical properties, and roughness of these stainless steels, produced by SLM ([ 19 , 20 , 21 ] −316L, [ 22 , 23 , 24 ]−630, [ 25 , 26 , 27 ]−420). SS 440C is also a martensitic stainless steel, but has high carbon content; it is used in applications where high hardness and corrosion resistance are necessary, such as bearings, knives and automotive parts [ 28 ].…”
Section: Introductionmentioning
confidence: 99%